INFLUENCE OF ADMINISTRATION, SUPERVISION AND CONTROL LOCAL PROPERTY AGAINST SECURITY REGIONAL PROPERTY OF PALEMBANG CITY - Ismail, Muhammad Ilham (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
This study aims to analyze the effect of administration, supervision and control of regional property on the security of regional property. The subjects in this study were managers of Palembang city property totaling 62 people. The research was conducted in 29 regional apparatus organizations in Palembang City in April-July 2021. Data analysis using multiple linear regression. The results of the multiple linear regression equation obtained the results Y=51.340+0.361X1-0.912X2+0.298X3, showing that if the administrative and regulatory variables are improved, it will have a positive effect on the success of securing regional property, but on the contrary, if the supervisory variable is increased, it will negatively affect the success of securing regional property. Respondents came from 29 regional apparatus organizations consisting of agencies and agencies under the Palembang City Government and by adding variables for regulating regional property.